THE INFLUENCE OF TOURIST ATTRACTION DEVELOPMENT, ATTRACTIVENESS AND PROMOTION ON TOURIST INTEREST (Case Study of Bur Telege Takengon Tourism, Aceh Tengah) - Ardi Sopian; Hamdiah; Siti Maimunah; Munandar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research aims to analyze the influence of tourist attraction development, attraction and promotion on tourist interest in visiting. Tourist attractions that are well developed, equipped with unique attractions and supported by effective promotions, can increase tourist interest. The research method used is quantitative with a survey approach, where data is collected through questionnaires distributed to tourists visiting the Bur Telege tourist attraction. The research results show that the development of tourist attractions, attractions and promotions have a positive and significant influence on tourist interest in visiting. These findings indicate that destination managers need to prioritize the development of tourist facilities and attractions to increase competitiveness and optimize promotion as the main support.